Disseminated intravascular coagulation in pregnancy: a case report - Lalu, Aneetta M.; Mathew, Rachel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Disseminated intravascular coagulation (DIC) is a life-threatening situation arising from a variety of obstetrical and non-obstetrical causes. Obstetrical causes include postpartum hemorrhage, placental abruption, preeclampsia, HELLP (hemolysis, elevated liver enzymes and low platelets) syndrome, retained stillbirth, septic abortion and intrauterine infection, amniotic fluid embolism and acute fatty liver of pregnancy. Prompt diagnosis and understanding of the underlying mechanism is essential for a favorable outcome. We report a successful pregnancy outcome in a multiparous woman with severe atonic postpartum hemorrhage following normal vaginal delivery managed by obstetric hysterectomy complicated with disseminated intravascular coagulation. Massive blood and blood products transfusion given. Serial monitoring of coagulation profile done- improved on postoperative day 3. Identification of risks and early diagnosis of DIC can prevent maternal morbidity and mortality. Team work and prompt treatment are essential for successful management.